Annual Plan 1995-96 Government of Punjab - Planning Commission (Planning Commission, 1995)
The above table reveals that the rural population in the State is 142.89 lakhs and the urban population is 59.93 lakhs. The maximum rural population in the State is in Amritsar district which is 16.51 lakhs and is followed by Gurdaspur district with 13.70 lakhs. the lowest population is in Fatehgarh Sahib district which is 3.51 lakhs. In terms of urban population Ludhiana District has 12.43 lakh population and is followed by Amritsar district with 8.54 lakhs population. the smallest district in terms of urban population is Mansa district with 0.85 lakh population.
Department of Planning Government of Punjab